2018
DOI: 10.1186/s12944-018-0845-y
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 and omega-6 fatty acid differentially impact cardiolipin remodeling in activated macrophage

Abstract: BackgroundThe macrophage plays an important role in innate immunity to induce immune responses. Lipid replacement therapy has been shown to change the lipid compositions of mitochondria and potentially becomes an alternative to reduce the inflammatory response.MethodsWe examined the effects of omega-6 arachidonic acid (AA), omega-3 eicosapentaenoic acid (EPA), and omega-3 docosahexaenoic acid (DHA) supplementation on the activated the macrophage cell line RAW264.7 via KdO2-lipid A (KLA). The mitochondrial card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…All but two (GpGro 34:2, GpGro 38:4) contained ω3 or ω6 PUFA (Fig 11C); and all increased in livers of WD-fed mice. GpGro are cardiolipin precursors and cardiolipin is a major mitochondrial matrix phospholipid [87, 88]. Interestingly, increases in mitochondrial ω3 and ω6 PUFA is associated with increased generation of reactive oxygen species ( ROS ) and oxidative stress is linked to NAFLD [89].…”
Section: Resultsmentioning
confidence: 99%
“…All but two (GpGro 34:2, GpGro 38:4) contained ω3 or ω6 PUFA (Fig 11C); and all increased in livers of WD-fed mice. GpGro are cardiolipin precursors and cardiolipin is a major mitochondrial matrix phospholipid [87, 88]. Interestingly, increases in mitochondrial ω3 and ω6 PUFA is associated with increased generation of reactive oxygen species ( ROS ) and oxidative stress is linked to NAFLD [89].…”
Section: Resultsmentioning
confidence: 99%
“…It is not immediately clear why mitochondrial function is impaired in SREBP1-deficient macrophages. However, a global reduction of phospholipids ( Figure 5 ) may account for the impaired mitochondrial function in SREBP1-deficient macrophages, as EPA-containing phospholipids are reportedly important for mitochondrial homeostasis in many cell types, including macrophages ( 33 , 34 ). In agreement with this, exogenous EPA increased levels of phospholipids, including phosphatidylglycerol (PG) species containing EPA at their sn-2 position EPA ( Figure 7 ), and increased expression of genes related to mitochondrial metabolism ( Figure 6F ).…”
Section: Discussionmentioning
confidence: 99%
“…The tendency of intracellular oxygen consumption rate was also higher in AA treated samples. In a previous study, it was shown that the 20-carbon EPA (20:5n-3) and AA prompted higher incorporation into the mitochondrial inner membranes than 22-carbon DHA [ 56 ]. Fatty acid oxidation occurs within mitochondria, the higher expression of PGC-1α under AA treatment may be involve in this process.…”
Section: Discussionmentioning
confidence: 99%